The Influence of Leadership Style on the Effectiveness of Financial Management in Education Quality Assurance Institution Department of Education - Ratu Noorita Achmad; Fitriani Fitriani (ILIN Institute, 2021)
This study aims to find out the effect of leadership style on the effectiveness of financial management at the Educational Quality Assurance Institute (LPMP). The research design used in this research is quantitative research methods. Descriptive statistical analysis is used with the intention of describing the effect of leadership style on financial management. The population as the subject of this research is the budget executor in the work unit in LPMP Gorontalo Province. The sampling method used was Simple Random Sampling. The results showed that the leadership style had a positive and significant effect on the effectiveness of financial management.